Empowering Senior Citizens: Utilization of ‘Jeeuni Bhaag’ Assets in Surkhet, Nepal - Malla, Trishna (NPRC Journal of Multidisciplinary Research, 2025)
"Jeeuni Bhaag" is an important social and financial security measures to the Nepali senior citizens, in which they legally keep some portion of property (such as land, cattle, house, gold, cash) in their custody. They can make self-decision to use such property when they are left uncared by families or if they want money for their good health, wellbeing, or any other social commitments. However, "Jeeuni Bhaag" exists as a social practice developed in Nepali society, which this research view as a home grown and customary law in Nepal. There is very limited academic research conducted to explore its socio-economic dimensions of “Jeeuni Bhaag”. This qualitative research explroes how "Jeeuni Bhaag" contributes to the empowerment of senior citizens in Surkhet, Nepal. I adopt qualitative research design using narrative inquiry method to explore the stories and lived experiences of four senior citizens in Surkhet. I explored that, "Jeeuni Bhaag" has empowered older-adults in financial decision making and autonomous enjoyment of their portion of property in their wellbeing and health. Jeeuni has contributed to ensure socio-economic security of senior citizens in Nepal through decision making, better health service, and financial independence. It needs proper acknowledgement through policies and regulations to connect with broader national and global development goals such as Nepal Social Security Fund, and SDGs. This empirical evidence is helpful to advocators of senior citizen campaigns, planners and policy makers’ in Nepal, and academicians to understand the importance of, "Jeeuni Bhaag" and mainstream it into wellbeing and welfare of senior citizens.